A Decoupled and Interoperable Architecture for Coordination in Ubiquitous Systems - Lima, Francisco F. P.; Rocha, Lincoln S.; Maia, Paulo H. M.; Andrade, Rossana M. C. (Anais do Simpósio Brasileiro de Componentes, Arquiteturas e Reutilização de Software (SBCARS); 2011: Anais do V Simpósio Brasileiro de Componentes, Arquiteturas e Reutilização de Software, 2011)
With the hardware technology advances, such as the smaller and more powerful computers and the progress of the data wireless communication, the Ubiquitous Computing has become reality. However, the development of ubiquitous systems still presents several challenges due to the great diversity and complexity of its requirements. Particularly in ubiquitous environments, where the dynamicity and heterogeneity of the devices and services are common features, the decoupled and interoperable coordination of activities performed by the system software agents is essential. Hence, this work proposes an architecture that provides means of coordination and interaction that are both decoupled and interoperable for the development of ubiquitous systems.